STATUS KEPEMILIKAN TANAH PEMBERIAN ORANGTUA KEPADA ANAK PEREMPUAN MELALUI PAUSEANG PADA MASYARAKAT BATAK TOBA DI KEC.DOLOK SANGGUL KAB.HUMBANG HASUNDUTAN - TIGOR SINAMBELA (PREMISE LAW JURNAL, 2014)
ABSTRACT ‘Pauseang’ is one of the types of gift before and after a daughter gets married. A profound research on the giving of land through ‘pauseang’ needed to be conducted since nationally the position of a daughter today tends to be equal to that of a son. Besides that, land as a gift cannot be separated from the prevailing rule of marga land. The research on the giving of land through ‘pauseang’ was conducted to find out the reason for giving land through ‘pauseang’ and to find out the status of a daughter’s ownership of the land. The research used judicial empirical analysis with descriptive analytic method. Based on the result of the research, it was found that the giving of land through ‘pauseang’ was done because the factors of love and affection, economy, and land as the identity for kinship and for family honor. The development of a daughter’s position as an heir nationally did not cause her to have property rights on land, given by her parents; she only had the right of use. Keywords : Daughter, Batak Toba, Pauseang